Factors influencing perforated appendicitis in a tertiary care hospital - A., Palachandra; R., Shashank; C. Y., Sreelatha (International Surgery Journal, 2017)
Background: Appendicitis is among the most common abdominal conditions requiring admission to emergency surgery departments. It has a life time risk of 6%. Untreated appendicitis may be complicated with development of gangrene or perforation, resulting in high morbidity and mortality rates in almost all age groups. The frequency of appendicitis may show variation by population, age, sex, socioeconomic status, and race. The objective of this study was to know the influence of some demographic factors on perforated appendicitis in a tertiary care hospital. Methods: A descriptive cross sectional was done in a teaching hospital which is a referral center. All the acute appendicitis cases admitted to the hospital between January 2015 to December 2016 were included in the study. A total of 532 acute appendicitis cases were diagnosed based on pathological features and were allocated to either the perforated or non-perforated appendicitis groups. Results: In our study total 532 cases were operated for appendicitis. Among that 294 (56%) were males and 238 (44%) were females with a ratio of 1.27:1.00. The mean age was 26.8±13.2 among non -perforated cases and 22.4±12.3 among perforated cases. In present study, maximum cases were in the age group 21-30 years and perforation was more among >50 years age group (23.3%). Conclusions: Perforation was higher among >50 years age group and in the patients from rural area which was found to be statistically significant. The reasons can be misdiagnosis, delayed diagnosis, financial and transportation problems.